Increased lymph node yield indicates improved survival in locally advanced rectal cancer treated with neoadjuvant chemoradiotherapy. (28th June 2019) - Wang, Yaqi; Zhou, Menglong; Yang, Jianing; Sun, Xiaoyang; Zou, Wei; Zhang, Zhiyuan; Zhang, Jing; Shen, Lijun; Yang, Lifeng; Zhang, Zhen
Abstract: Purpose: It is recommended for colorectal cancer to harvest at least 12 lymph nodes (LNs) during surgery to avoid understaging of the disease. However, it is still controversial whether it is necessary to harvest from locally advanced rectal cancer (LARC) patients who underwent neoadjuvant chemoradiotherapy (neo‐CRT). The impact of lymph node yield (LNY) on prognosis in LARC patients was analyzed. Materials/Methods: In total, 495 LARC patients who underwent neo‐CRT in 2006‐2015 were analyzed. After examining clinicopathological distribution differences between the LNY subgroups (with the threshold of 12), univariate and multivariate Cox survival analyses were performed. Survival plots were obtained from Kaplan‐Meier analyses. Similar subgroup analyses were performed according to the tumor regression grade (TRG) and metastatic status of post‐operational LNs. Results: Of the 495 patients, 287 (57.98%) had an LNY of less than 12. Nearly no significant clinicopathological difference was found between the LNY subgroups, including the TRG scores. Multivariate survival analysis demonstrated that at least 12 LNs examined was an independent prognostic feature of good overall survival (OS), disease‐free survival (DFS), and distant metastasis free survival (DMFS), but not local recurrence free survival (LRFS). However, in the subgroup analyses, no association was found between LNY and prognosis in patients with good TRG scores (0‐1) or negative LNs. Conclusions: For LARC patients treated with neo‐CRT, an LNY of at least 12 indicated an improved survival. Decreased LNY was not related to better tumor regression. It suggests that a sufficiently high LNY is still required, especially in those with a potentially poor tumor response. Abstract : Increased lymph node yield (LNY ≥ 12) was an independent good prognostic factor in locally advanced rectal cancer patients treated with neoadjuvant chemoradiotherapy. Lower LNY was not associated with good tumor response. They probably still need a sufficiently high LNY, especially those with a potentially poor tumor response.